'The World of Art': a video course for engineers. (4th August 2014) - Borodiouk, Vitali P.; Mikryukova, Nadejda A.
Within the framework of rendering the system of engineering education more oriented towards the humanities, a dedicated video film course has been developed at the Centre for Novel Information Technologies of the Moscow Power Engineering Institute. This educational course consists of four parts dealing with the same topic: the story of an outstanding phenomenon in the history of Russian culture, known as 'The World of Art' (Mir Iskusstva). The material is presented in a fascinating way; however, it adheres strictly to the facts. Making use of ample illustrative material, the course familiarises students with the social, exhibitional and artistic activity of the union and magazine called 'The World of Art', its influence on the tranformation of Russian culture, and the development of avant–garde artistic movements in Russia and the West at the turn of the last century. Each part consists of a video film recorded on a standard videocassette.